Study of economically valuable traits and technological properties in maize from the Zea mays L. collection of VIR - M. R. Gonikova; V. I. Khoreva; V. G. Goldshtein; L. P. Nosovskaya; L. V. Adikaeva; E. B. Khatefov (Труды по прикладной ботанике, генетике и селекции)
Background. Innovative technologies for deep processing of grain are widely used in maize grain processing with the release of the grain germ for subsequent extraction of oil and starch from it or production of sugar substitutes in the form of fructose syrup and alcohol, bakery or feed protein. A search for economically valuable sources of maize starch, useful byproducts of its processing, and natural modification of starch for deep processing is vital.Materials and methods. Ten high-starch maize accessions from the VIR collection, isolated by IR spectrometry, were studied. Starch content was measured according to GOST 10845-98, GOST 13586.5-93, GOST 10847-74 and GOST ISO 6647-1-2015 standards. Processing of grain into starch and assessment of the content of amylose and byproducts were carried out at the All-Russian Scientific Research Institute for Starch Products in 2018 according to L. P. Nosovskaya et al. The actual content of starch and its byproducts during deep grain processing was determined. The values of the actual percentage of dry matter (DM, %) in grain, mass fraction of starch, ash content, as well as the yield of extract, pulp, embryo, gluten, process water and starch were determined.Results. Accessions with a high yield of starch (k-4520, k-9301 and k-24730), germ (k-4520. k-8785 and k-24731), pulp (k-4520, k-8785, k-9991 and k-24732) and protein (k8785) were identified as well as those with a percentage of amylopectin in starch above 82% (k-24730 and k-24733) and 100% (k-5461 and k-9991), and amylose above 30% (k4520 and k-9301).Conclusion. Of practical interest in terms of the actual yield of starch (% DM in grain) are accessions k-4520, k-9301, k-24730, k-9991, k-5461 and k-4520. According to the results of breeding tests, accessions k-24730, k-24732 and k-24733 had the following values of starch harvest calculated for grain yield: 4.66, 4.41 and 4.18 t/ha, respectively.